2021
DOI: 10.1016/j.eclinm.2021.101089
|View full text |Cite
|
Sign up to set email alerts
|

Serum ω-6/ω-3 polyunsaturated fatty acids ratio and diabetic retinopathy: A propensity score matching based case-control study in China

Abstract: Background Optimal ω-6/ω-3 polyunsaturated fatty acids ratio (PUFAR) is reported to exert protective effects against chronic diseases. However, data on PUFAR and diabetic retinopathy (DR) remains scarce. We aimed to thoroughly quantify whether and how PUFAR was related to DR as well as its role in DR detection. Methods This two-centre case-control study was conducted from August 2017 to June 2018 in China, participants were matched using a propensity score matching algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To avoid various types of bias due to confounding factors or uneven data distribution, PSM was used to match the DR and DM groups according to a 1:1 ratio for age, sex, body mass index (BMI) and glycated hemoglobin (HbA1c), and to match the DM and healthy control groups were matched for age, sex and BMI, and 69 blocks were obtained for inclusion in the analysis. The sample size was sufficient to meet statistical requirements and guarantee the reliability of our findings, and the sample size and power estimations were specifically described in our previous studies [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…To avoid various types of bias due to confounding factors or uneven data distribution, PSM was used to match the DR and DM groups according to a 1:1 ratio for age, sex, body mass index (BMI) and glycated hemoglobin (HbA1c), and to match the DM and healthy control groups were matched for age, sex and BMI, and 69 blocks were obtained for inclusion in the analysis. The sample size was sufficient to meet statistical requirements and guarantee the reliability of our findings, and the sample size and power estimations were specifically described in our previous studies [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was a two-center case-control study, which is a propensity score matching (PSM) based lipidomics study conducted in China between August 2017 and June 2018. Detailed information on this study design and participants can be found in our previous works ( 15 17 ). In brief, a total of 195 patients with type 2 diabetes (T2D) patients (83 with DR and 112 without DR) aged over 35 years and free from type 1 diabetes, cardiovascular diseases, cerebrovascular diseases, hyperkalemia, cancers, infectious diseases, or other chronic systemic diseases were recruited from two affiliated hospitals of Wenzhou Medical University and Anhui Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study design, enrolment of participants and other information are reported in our previous work. 10,15,16 Briefly, in this two-centre, PSMbased case-control study, a total of 195 patients with type 2 diabetes (T2D) were enrolled from the departments of endocrinology in the Second Affiliated Hospital of Wenzhou Medical University and the First Affiliated Hospital of Anhui Medical University from August 2017 to June 2018. Among them, 83 cases (T2D with DR) and 112 controls (T2D without DR) were diagnosed by two professional experienced ophthalmologists using clinical diagnostic criteria and fundus examination images.…”
Section: Study Participantsmentioning
confidence: 99%
“…1,2 It has been confirmed that DR silently progresses over several years without the individual's awareness, ultimately leading to severe vision impairments and a significant reduction in their overall quality of life. 3 Previous studies have revealed that DR can be detected in more than 35% of patients with diabetes, [4][5][6] and has become a major health problem worldwide, as well as continuously leading to an apparently elevated global disease burden. 7 The exact mechanism of DR remains unclear; however, evidence suggests that several biological processes, including immune response, oxidative stress, metabolic disorders, neuronal apoptosis and the release of inflammatory mediators, play a crucial role in both the initiation and progression of DR. [8][9][10] Weighted gene co-expression network analysis (WGCNA) has become an important, valuable and frequently used bioinformatics analytical approach, 11 after being proposed by Zhang and Horvath in 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation